2018
DOI: 10.1136/archdischild-2018-315643
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus and parechovirus meningitis in infants younger than 90 days old in the UK and Republic of Ireland: a British Paediatric Surveillance Unit study

Abstract: ObjectivesThis study aimed to prospectively collect detailed clinical information for all enterovirus (EV) and human parechovirus (HPeV) meningitis cases in infants aged <90 days in the UK and Ireland.Participants, design and settingProspective, active national surveillance during July 2014 to July 2015 through the British Paediatric Surveillance Unit. Reporting paediatricians completed questionnaires requesting information on clinical presentation, investigations, management and outcomes at hospital discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 31 publications
6
83
0
Order By: Relevance
“…In the United Kingdom, the largest follow‐up study of EV meningitis included 668 cases in infants less than 3 months old and followed up till 12 months of life . No infants had hearing loss.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United Kingdom, the largest follow‐up study of EV meningitis included 668 cases in infants less than 3 months old and followed up till 12 months of life . No infants had hearing loss.…”
Section: Resultsmentioning
confidence: 99%
“…In the United Kingdom, a prospective national study using questionnaires completed by paediatricians managing 35 HPeV cases less than 3 months old showed that none had SNHL or neurodevelopmental delay at 12‐month follow‐up . In England during 2016, a retrospective study using a similar questionnaire‐based methodology showed that 5% (5/106) of cases had seizures beyond hospital discharge, but again, there was no evidence of SNHL or neurodevelopmental delay…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent study from the UK showed that testing CSF samples from viral PCR without any screening criteria in children under aged < 5 years who presented with sepsis‐like illness or meningitis increased the detection of EV and/or HPeV from 3.1% to 26.4% . A recent BPSU study with 703 cases of EV and HPeV related meningitis demonstrated that >50% of the infants (aged <3 months) had absent CSF pleocytosis and low inflammatory markers . Consequently, we now recommend PCR testing locally on all infants <6 months old, irrespective of CSF WCC count (adjusted or unadjusted) where viral meningitis is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…2 is more than double that for bacterial meningitis in this age group. 3 The same study showed that <1% of infants in the EV meningitis group developed significant complications (n = 4) or died of their infection (n = 2). 3 All infants with HPeV meningitis survived without any sequelae.…”
Section: Introductionmentioning
confidence: 90%